Modified Pickup And Delivery-Capacitated Heterogeneous Vehicle Routing Problem Untuk Perancangan Rute Dan Alokasi Kapal - Vitovern Joey Susila; Siana Halim (Jurnal Titra, 2023)
This articles discusses the problem of route design and demand allocation for each vessel at shipping company, it intends to determine the most efficient routes in terms of overall total distance and utility for each vessel. The proposed model is the modified Heterogeneous Fleet Vehicle Routing Problem to address the pickup and delivery problem. The approach utilizes transition probability to consider the company's historical route generation experience. It also combines distance and demand between ports to handle the two objective functions. This model can create beter routes and vessel allocations with respect to total distance and average ship utility, as indicated by the comparative analysis. Implementing the model with demands at the homebases in Jakarta and Surabaya reduced the total distance by up to 1160 N.Miles and increased average utility by 20% from the previous routes. However, the model only proposes using ships according to the efficient number for operation and is currently limited to the process of only one homebase. The current model has been automated into a program that functions as a decision support system for the company to determine the best or near-optimal routes.